2013
DOI: 10.1021/jf400740p
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Carbon Dioxide Extraction of Fucoxanthin from Undaria pinnatifida

Abstract: Undaria pinnatifida, commonly known as wakame in Japan, is one species of brown seaweeds containing valuable bioactive organic compounds such as fucoxanthin, a carotenoid, which has numerous functional properties. However, most of the seaweeds that do not meet strict quality standards are normally discarded as wastes or returned to the sea, a situation which is becoming an environmental concern. In this research, supercritical carbon dioxide (SCCO₂) extraction was investigated for the isolation of fucoxanthin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…Broad ranges have been reported for all three of these parameters, using various protocols. Grosso et al (2015) reviewed extraction methods ranging from pH 3.8 to 8.5; Bidigare et al (2005) reported using 0°C for up to 24 h, Billakanti et al (2013) 37°C for 2 h at pH 6.2, Quitain et al (2013) 40°C for 3 h, Sivagnanam et al (2015) 45°C for 2 h, Roh et al (2008) 49.85°C for 50 min, and Shang et al (2011) pigment-containing thylakoids in the blades, which function as the photosynthesis engines of macroalgae, compared to the stipe or holdfasts which have structural functions. Photoprotection of thallus regions near the ocean surface against ultraviolet light is another function of fucoxanthin in the blades, where it exerts its powerful antioxidant effect (Lobban and Harrison 1994;Stengel and Dring 1998;Hurd et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Broad ranges have been reported for all three of these parameters, using various protocols. Grosso et al (2015) reviewed extraction methods ranging from pH 3.8 to 8.5; Bidigare et al (2005) reported using 0°C for up to 24 h, Billakanti et al (2013) 37°C for 2 h at pH 6.2, Quitain et al (2013) 40°C for 3 h, Sivagnanam et al (2015) 45°C for 2 h, Roh et al (2008) 49.85°C for 50 min, and Shang et al (2011) pigment-containing thylakoids in the blades, which function as the photosynthesis engines of macroalgae, compared to the stipe or holdfasts which have structural functions. Photoprotection of thallus regions near the ocean surface against ultraviolet light is another function of fucoxanthin in the blades, where it exerts its powerful antioxidant effect (Lobban and Harrison 1994;Stengel and Dring 1998;Hurd et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…FX has strong antioxidant properties against obesity and inflammation (4042). FX reduces the levels of reactive oxygen species (ROS), damage and apoptosis (43).…”
Section: Introductionmentioning
confidence: 99%
“…[111] , Synechococcus sp. [116] , Undaria pinnatifida [19,20] has also been reported and shown in Table 2. Overall, SFE has been shown to be an excellent technique for the selective extraction of carotenoids from a wide range of algae and microalgae.…”
Section: Nonconventional Extraction Of Carotenoidsmentioning
confidence: 99%
“…In particular, fucoxanthin is a characteristic orange xanthophyll, which is abundant in several brown seaweeds including Undaria pinnatifida [18,19,20,21,22,23], Hijikia fusiformis [24], Laminaria japonica [21,25,26], Sargassum sp. [27,28,29,30,31,32], and Fucus sp.…”
Section: Introductionmentioning
confidence: 99%